The use of greenhouses in Brazil: advantages and disadvantages - de Oliveira, Maria Regina Vilarinho (Pesquisa Agropecuaria Brasileira, 1995)
As, in Brazil, the number of greenhouses has been increasing, the objective of this research was to give information about the structures being utilized in the country, to record the main pests occurring inside these environments, in the different regions, and to report the advantages and disadvantages of the use of these artificial environments. A questionnaire was sent to different institutions, from August 1992 to December 1993. The collected data were normalized to 100. One hundred nineteen replies were obtained from the survey. The sampled area covered a surface of 20,755 m2 with glasshouses, and, 63,474 m2 with plastic houses. Among the styles, even-span greenhouses have been used in 46.22%, and polyethylene was the most used material. As a consequence of the favourable artificial ecossystem, in 88.04% of the houses the presence of pests and diseases was detected and chemical control was used in 91.30% of the cases.